Spatial and Seasonal Patterns of Tick Infestations in Kassena-Nankana Livestock - Seth Offei Addo; Ronald Essah Bentil; Bernice Olivia Ama Baako; Jane Ansah-Owusu; Christopher Nii Laryea Tawiah-Mensah; Eric Behene; Victor Asoala; James C. Dunford; John Asiedu Larbi; Philip Kweku Baidoo; Michael David Wilson; Joseph W. Diclaro; et al. (Veterinary Medicine International)
The ability of ticks to adapt to different ecological zones, coupled with the spread of infectious pathogens negatively affects livestock production and thus, there is a need for better control strategies. However, control measures within a geographical region can only be effective if there is available information on tick population dynamics and ecology. This study focused on ticks infesting livestock in the Kassena-Nankana Districts of the Upper East Region of Ghana. The ticks were morphologically identified, variables such as season, animal host, and predilection sites were recorded, and the data were analyzed using STATA version 13. Out of 448 livestock examined, tick infestation in cattle was (78.60%), followed by sheep (25%) and goats (5.88%). A total of 1,550 ticks including nymphs (303) and adults (1,247) were collected. Adult ticks were found to be significantly associated with season (p<0.001), with a high burden in the wet season. The nymph burden and body parts of livestock hosts were significantly associated with more nymphs collected from male animals than females (p<0.001). Three genera of ticks, Amblyomma (62.97%), Hyalomma (18.71%), and Rhipicephalus (18.32%) were morphologically identified with the most predominant tick species recorded as Amblyomma variegatum (62.97%). Matured A. variegatum was sampled primarily in the wet season with their predilection site as the udder/scrotum (p<0.001). However, adult Hyalomma truncatum was observed to have a significant association with the anal region (p<0.001). Findings from this study are essential for formulating tick control measures to prevent the spread of infectious pathogens.